Analisis Efesiensi Penggunaan Modal Kerja Perusahaan dengan Rasio Keuangan pada Bank Negara Indonesia Tbk Tahun 2018 – 2022 - Rasnawati, Atti; Choiri, Miptahul; Khoiroh, Nadiatul; Delima, Ratumas Hartha (Universitas Batanghari Jambi, 2024)
This research focuses on capital issues in companies which are seen based on the financial performance of Bank Negara Indonesia Tbk with liquidity ratios, profitability ratios and solvency ratios in 2018-2022. The results of the research are that the liquidity ratio with the FDR ratio and the current ratio have quite good capital efficiency in paying the company's liquidity, the profitability ratio with the CAR, DER and DAR ratios shows that the company has been able to process and generate profits to carry out the company's operational activities and increase the capital owned by company so that capital efficiency is met. Meanwhile, the Solvency Ratio, namely ROA, ROE and NPM, the company has the ability to manage capital and reduce the level of bankruptcy in the future.